A side‐by‐side comparison of CPV module and system performance. (23rd February 2016) - Muller, Matthew; Marion, Bill; Kurtz, Sarah; Ghosal, Kanchan; Burroughs, Scott; Libby, Cara; Enbar, Nadav
Abstract: A side‐by‐side comparison is made between concentrator photovoltaic module and system direct current aperture efficiency data with a focus on quantifying system performance losses. The individual losses measured/calculated, when combined, are in good agreement with the total loss seen between the module and the system. Results indicate that for the given test period, the largest individual loss of 3.7% relative is due to the baseline performance difference between the individual module and the average for the 200 modules in the system. A basic empirical model is derived based on module spectral performance data and the tabulated losses between the module and the system. The model predicts instantaneous system direct current aperture efficiency with a root mean square error of 2.3% relative. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A side‐by‐side comparison is made between a CPV module and system with a focus on quantifying system performance losses. The quantified individual losses are in good agreement with the total loss seen between the module and the system. The largest individual loss of 3.7% relative is due to the baseline difference between the individual module and the average for the 200 system modules. An empirical model is derived, which predicts instantaneous system DC aperture efficiency with a RMSE of 2.3%.